Beam-facing material selection for mitigation of residual doses in the HEBT of IFMIF-DONES - Francisco Ogando; Llorenç Macia; Victor Lopez; Ivan Podadera; Daniel Sanchez-Herranz (Nuclear Materials and Energy, 2024)
IFMIF-DONES will be an irradiation facility based on a 40 MeV deuteron accelerator. Unavoidable beam losses along the accelerator result in deuterium interactions with the beam facing materials of the vacuum beam pipe, some of them leading to material activation. The initial design of the beam pipe was based on stainless steel, but an evaluation of the residual doses from the pipe showed high values after operation of the accelerator. The accelerator beam line must be periodically maintained, and excessive cooling times for reaching acceptable dose levels may result in poorer availability of the facility. A deeper study of the High Energy Beam Transport line (HEBT) showed that a direct reaction between deuterons and iron in steel resulted in the production of Co-56, with a half-life of 77 days. This radioisotope is the main source of the radiation and makes it impractical to wait for a proper attenuation of the radiation field. A redesign of beam line elements has been performed to avoid the presence of stainless steel as a beam facing material and to replace it with aluminum where possible, resulting in faster decay of residual doses. This work contains a summary of the nuclear analysis performed for the computation of residual doses with stainless steel beam pipe, stressing the uncertainties of the calculations, based on the limited availability of nuclear data for the relevant nuclear reaction Fe56 (d,2n). The proposed replacement of element materials is also described, and an updated nuclear analysis shows the reduction of residual radiation, and its impact on possible maintenance operations.